Design insights for upscaling spontaneous microfluidic emulsification devices based on behavior of the Upscaled Partitioned EDGE device. (February 2023) - ten Klooster, Sten; Berton-Carabin, Claire; Schroën, Karin
Graphical abstract: Highlights: We tuned droplet size to 3.5, 7 and 30 µm by device geometry and process design. Relatively high oil throughputs of 0.3, 0.5 and 4 mL/h rapeseed oil were obtained. The devices are flexible in the choice of surface-active ingredients. Device design including its sub-structure is key to obtain high production rates. Abstract: Microfluidic emulsification has the potential to produce emulsions with very controlled droplet sizes in a subtle manner. To support in unleashing this potential, we provide guidelines regarding upscaling based on the performance of Upscale Partitioned EDGE (UPE) devices, using rapeseed oil as the to-be-dispersed phase and whey proteins as the emulsifier. The UPE5x1 device (11, 000 droplet formation units (DFUs) of 5 × 1 µm) produced 3.5-µm droplets (CV 3.2 %) at 0.3 mL/h; UPE10x2 (8, 000 DFUs of 10 × 2 µm) produced 7-µm droplets (CV 3.2 %) at 0.5 mL/h, and at higher pressures, 32-µm droplets (CV 3–4 %) at 4 mL/h. These productivities are relatively high compared to those of other devices reported in literature (e.g., Microchannel, Tsukuba and Millipede, Harvard). Based on these results, and on others from literature, we conclude that: (1) the continuous phase channel dimensions need to be chosen such that they allow for gradual filling of this channel with droplets without decreasing the pressure over the droplet formation units significantly; (2) the dispersed phase supply channel design should create a wide stable droplet formation pressure range to increase productivity; and (3) higher productivities can be obtained through the choice of the ingredients used; low viscosity dispersed phase and an emulsifier that increases the interfacial tension without negatively affecting device wettability is preferred (e.g., whey protein outperforms Tween 20). These results and design guidelines are expected to contribute to the first food emulsion products prepared with microfluidics.